Challenges faced by modern foreign language teacher trainees in using handheld pocket PCs (Personal Digital Assistants) to support their teaching and learning - Wishart, Jocelyn (ReCALL (Cambridge, England), 2008)
This study addresses the challenges faced by Modern Foreign Language teacher trainees when asked to investigate the potential of a Personal Digital Assistant to support them both in their learning and in their teaching during their training year. Personal Digital Assistants (PDAs) such as the Windows Pocket PCs used in this study have previously been found supportive by trainees in other professions with a large information content. Modern Foreign Languages (MFL) was chosen as the subject for this investigation as a particularly wide range of potential opportunities specific to MFL was foreseen. These opportunities ranged from supporting student teachers' learning by enabling access to email and other internet resources wherever they were based to enabling ‘on the spot’ audio or video recordingto support their teaching. For this investigation, seven student teachers from an MFL initial teacher training programme were loaned PDAs for the duration of their course. This paper reports on interviews conducted at the end of the training year with six of the student teachers in order to elicit their views on the PDAs they were loaned. They were all experienced information technology users and willing to explore the devices but there had always seemed to be a preferred alternative technology available either at home or in the classroom. Their reports shed much light on the current climate in schools and subject culture pressures as interpreted by student teachers in MFL departments but told us only a little about the functionality of a PDA and how it can support mobile assisted language learning. The socio-cultural context within the MFL departments where the trainees were placed meant that they did not feel comfortable about exploring the PDA functionality. They were not yet confident in their pedagogical identities and mostly felt they could not disrupt the established practice with the novel technology. However, when the devices were used, applications that appeared most effective in supporting learning to teach MFL with PDAs were those that enabled the capture of on-the-spot events and reflections. This could be either through the inbuilt recording functions, especially video, or by making notes using either the on-screen keyboard or by handwriting recognition.